Mental- and physical-health comorbidity are strongly associated in idiopathic inflammatory myopathies: a multinational cross-sectional e-survey - Samuel Katsuyuki Shinjo; Lekshmi Minikumari Rahulan; Meera Shah; Anchit Chauhan; Suhana Hussain; Paula Jordan; Meghna Lama; Oladipo Kunle Afolayan; Vincenzo Venerito; Tamar B. Rubinstein; Ioannis Parodis; Elena Nikiphorou; et al. (Rheumatology International, 2026)
Abstract Comorbidities are associated with morbidity, function, and survival in idiopathic inflammatory myopathies (IIM), but subtype-specific patterns, mental-physical comorbidity relationships, and patient-reported outcomes remain incompletely characterized. We hypothesized that multimorbidity in IIM is heterogeneous, associated with demographic, clinical, and psychosocial factors, and linked to differences in physical function and fatigue. We studied 1028 adults with self-reported, specialist-confirmed IIM. Comorbidities were assessed using the Functional Comorbidity Index and categorized into basic, complex, mental-health, and autoimmune domains. Logistic regression identified factors associated with mental- and physical-health comorbidity; clustering defined comorbidity patterns. Participants were predominantly female (71.3%), median age 59.0 years. Overall, 46.7% had basic multimorbidity, 15.4% complex multimorbidity, 33.6% mental-health comorbidity, and 14.7% autoimmune multimorbidity. Interstitial lung disease was concentrated in anti-synthetase syndrome (50.7%) and polymyositis (42.6%), while hypertension (37.8%) and malignancy (35.0%) were concentrated in inclusion body myositis. Chronic pain/fatigue syndromes were associated with mental-health burden (63.2% vs. 27.5%, p < 0.001). Mental-health comorbidity was associated with younger age (OR 0.98/year), complex multimorbidity (OR 2.85), immunosuppressive therapy (OR 1.53), and lower family support (OR 0.94/unit). Physical-health comorbidity was independently associated with older age (OR 1.05/year), mental-health comorbidity (OR 3.96), and overlap myositis (OR 3.33). Clustering identified three multimorbidity profiles: low-burden (49.3%), cardiometabolic/malignancy-predominant with low mental-health burden (22.9%), and pain-fatigue/mental-health-predominant (27.7%), which differed significantly in physical function and fatigue. Multimorbidity in IIM is common, heterogeneous, and shows a strong concurrent relationship between mental- and physical-health comorbidity, supporting integrated mental-health screening and subtype-tailored surveillance.